Trajectories of Alcohol Use over the Life Course in the Add Health - Evans, Sara Z. (Journal of developmental and life-course criminology, 2024)
Alcohol use can vary across the life course. However, to date, too few studies have used panel data to look at patterns of alcohol use longitudinally. This study utilizes all five waves of the National Longitudinal Study of Adolescent to Adult Health (Add Health) and group-based trajectory modeling (GBTM) to describe and contrast longitudinal variations in alcohol use between females and males starting in middle adolescence and ending in when the respondents are in their late 30 s (N = 7295). The results show different patterns of alcohol use between females and males across the life course. For males and females, access to alcohol in their homes predicted membership in higher-level drinking groups, while peer drinking and objective evidence of alcohol in the home were more impactful for males. Results also allude to alignment with recent research showing a narrowing gender gap in alcohol consumption. Further analyses show differences between these groups in variables that shape trajectory group membership. Results indicate the need for policies that are sensitive to differences across sociodemographic groups such as race, gender, and SES, as well as the need for preventive efforts in early adolescence, especially those that include family-based interventions to target risk and protective factors.